2014
DOI: 10.1212/wnl.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Current practices in feeding tube placement for US acute ischemic stroke inpatients

Abstract: Objective: We sought to identify current US hospital practices for feeding tube placement in ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
2
34
1
2
Order By: Relevance
“…However, in our study length of stay was longer for minority patients compared to whites (median 12 vs 8 days), precluding the possibility that white patients were given more time to recover swallowing function during their hospitalization. Our findings are consistent with a recent study describing racial disparities in PEG placement after ischemic stroke 26 ; however, some of the observed disparities may at least in part be due to residual confounding by education level, another commonly employed surrogate of SES. Since the NIS does not collect information on level of education, we were unable to further test this hypothesis in our dataset.…”
Section: Discussionsupporting
confidence: 91%
“…However, in our study length of stay was longer for minority patients compared to whites (median 12 vs 8 days), precluding the possibility that white patients were given more time to recover swallowing function during their hospitalization. Our findings are consistent with a recent study describing racial disparities in PEG placement after ischemic stroke 26 ; however, some of the observed disparities may at least in part be due to residual confounding by education level, another commonly employed surrogate of SES. Since the NIS does not collect information on level of education, we were unable to further test this hypothesis in our dataset.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in part contradictory to previous findings that black and Hispanic ischemic stroke patients have higher risks for PEG tube placements than white patients. 17 In our study, patients with and without PEG tube placements showed significant differences in race distribution based on univariate analyses. However, after adjusting for treatment, provider and environment characteristics, race was not significant for 30-day readmissions.…”
Section: Discussionmentioning
confidence: 53%
“…In a recent study by George et al examining feeding tube placement in ischemic stroke patients, the authors suggest that a decision aid to deliver evidence-based options and inform families/patients about outcomes in dysphagia after stroke would greatly improve care. 73 Development of decision aids for common neurocritical care situations will have a large impact on improving the quality of shared decision making and potentially reducing conflict in the NICU.…”
Section: Shared Decision Making With Surrogatesmentioning
confidence: 99%